Association between delivery hospitalization blood pressure and severity of postpartum admissions for hypertension - Mindy Pike; Judy Han; Leah Chen; Catherine M. Albright; Raj Shree (PLoS ONE, 2026)
Background Hypertension is a leading cause of postpartum admission (PPA), but whether blood pressure (BP) at discharge from delivery hospitalization is associated with PPA severity is unknown. Furthermore, detailed characterization of presentation, management, and progression of hypertensive disorders of pregnancy (HDP) during PPA is lacking. Methods Retrospective study of PPAs for hypertension from 2016–2021. Exposure was highest BP within 24 hours of discharge from delivery hospitalization, classified as normal (<140/90 mmHg) or elevated (≥140/90 mmHg). The primary outcome was disease severity, measured by an aggregate “Severity Score” based on severe criteria for HDP. PPAs were further characterized by symptoms, interventions, and HDP progression. We also calculated the proportion of de novo postpartum HDP. Results Among 132 patients with PPA for hypertension, 76 had normal BP and 56 had elevated BP at discharge. Severity did not differ between groups. Median time to PPA was 5 days (IQR: 3–8) and 3 days (IQR: 1–5) for the normal and elevated BP groups, respectively (β –1.59, 95% CI –3.06, –0.12). Headache was the most frequent presenting symptom. HDP diagnosis worsened in 49% of cases. 27% experienced de novo postpartum HDP. Conclusions BP at discharge was not associated with PPA severity but was linked to earlier presentation. Close to half had worsening of HDP, while de novo hypertension accounted for over a quarter of PPAs. This underscores the need for earlier identification of postpartum hypertensive complications and determination of optimal BP targets. New onset hypertension represents a substantial proportion of PPAs, representing necessary admissions, rather than re-admissions.